P489 Are patients with inflammatory bowel disease receiving an adequate immunisation?. (15th January 2020) - Simian, D; Núñez, P; Flores, L; Figueroa, C; Ibáñez, P; Kronberg, U; Lubascher, J; Pizarro, G; Quera, R
Abstract: Background: Inflammatory Bowel Disease (IBD) treatment may increase the risk of infections. Vaccines are part of the comprehensive IBD patient care. The aim of this study was to describe indications and adherence of immunisations in IBD and identify possible associated factors. Methods: A cross-sectional, analytic study was conducted in patients from an IBD Program of a tertiary centre in Chile, between April – June 2019. Demographic and clinical data were obtained from the hospital IBD registry, approved by the local IRB. Patients were asked to answer a vaccine survey and complementary information was obtained from the National Immunization Registry. Descriptive and association statistic were used ( χ 2 ; p <0.05). Results: A total of 243 patients were included (Table 1). The influenza vaccine rate has significantly increased (Figure 1), reaching 67% in 2019, being higher in women (66% vs. 34%; p 0.045) and patients in biological therapy (BT) (29% vs. 14%; p 0.011) (Table 1). Vaccination rates are shown in Figure 2. Combination of Influenza/Hepatitis B/Pneumococcus vaccines was administered in 56 patients (23%), significantly higher in patients with BT and with fewer years of IBD. Forty patients received a live virus vaccine, 18% were on immunomodulatory treatment. The survey showed that 57 patients (23%) have not been immunised with any vaccine, mainly due to lack of time, lack of medical prescription and high cost. Conclusion: In this cohort, vaccination rates are low, however, adherence to Influenza vaccine has increased. Immunisation should be considered early by the multidisciplinary team, educating patients about its importance.